(untitled) (Journal of Social Sciences Review, 2022)
Bangladeshi novelist Fariha Roisin wrote Like a Bird (2020). Alyssa, the novel’s protagonist, has lost her beauty and charm due to society’s norms. Taliya narrates the protagonist’s life. Life depends on society’s standards, which lead to death, yet empowerment is needed to survive. Textual analysis underpins this qualitative investigation. Grice Atkinson’s (1970) view on radical women’s rights and snatching is accepted. Radical feminism shows how society treats women as sexual objects and attempts on their lives. Women are subjugated in society. Radical feminism investigates how men snatch women’s rights. This theory suggests that women as a class require participation in social politics to overcome life’s challenges. Radical feminism in the novel is examined in the study. The findings showed Alyssa’s struggle to break her habit, and living way requires a new life despite the social constraints.